Simulation of Tsunami Waves Generated by Landslide Movements on a Flat Bottom - Sulvianuri, Rani; Setyowisnu, Glagah Eskacakra; Pudjaprasetya, Sri Redjeki (Journal of the Indonesian Mathematical Society, 2025)
Disasters like tsunamis are typically triggered by tectonic earthquakes, volcanic eruptions, or landslides. Tsunami waves can hit the coast with enormous energy, causing great damage. This study focuses on landslide-generated wave phenomena; the analytical formula of the linear dispersive model is adopted and used to simulate the development of free surface waves due to bottom landslides. Various types of landslide motion were simulated over a flat bottom depth and the resulting surface wave forms were examined and compared with the far-field leading wave type of solution. In addition, the effect of wave dispersion on the resulting wave pattern was investigated.